Pengaruh Persepsi Return, Persepsi Risiko, Dan Literasi Keuangan Syariah Terhadap Keputusan Berinvestasi Generasi Z Kota Jambi Pada Saham Syariah - Naswaa Hasyim; Lucky Enggrani Fitri; Aditya Pratama (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the effect of perceived return, perceived risk, and Islamic financial literacy on the investment decisions of Generation Z in Jambi City regarding Islamic stocks. This study used a quantitative approach with purposive sampling. Data were collected through questionnaires and analyzed using PLS-SEM. The results show that perceived return and Islamic financial literacy have a positive and significant effect on investment decisions, while perceived risk has no significant effect.